Religious Doubt, Financial Strain, and Depressive Symptoms Among Older Mexican Americans - Krause, Neal M. (2011)
PURPOSE: A number of studies suggest that positive aspects of religion (e.g., social support from fellow church members) help older people cope more effectively with stress. However, researchers have known for some time that there are negative as well as positive facets of religion. This suggests that instead of enhancing coping efforts, religion may also exacerbate the effects of stress. The purpose of this study was to see if one negative aspect of religion (i.e., religious doubt) exacerbates the effects of financial strain on depressive symptoms among older Mexican Americans. METHODS: A nationwide survey of 1,005 older Mexican Americans was conducted. Measures of religious doubt, financial strain, and depressive symptoms were administered. RESULTS: The findings suggest that the effects of financial strain on depressive symptoms are stronger for older Mexican Americans who have more doubts about religion. CONCLUSIONS: This study explores aspects of religion that have received relatively little attention in the literature (i.e., religious doubt). Moreover, the data were provided by members of an ethnic group that have been largely overlooked by researchers who study religion (i.e., older Mexican Americans). Taken together, these study attributes help provide greater balance in the literature on religion and mental health in late life.